Ecological∼Enactivism Through the Lens of Japanese Philosophy - McKinney, Jonathan (Frontiers in Psychology, 2020)
The alliance between the enactive and ecological schools is well established, but their differences are not well understood. Broadly speaking, Enactive Cognitive Science focuses on autonomy and the rejection of mind-body dualism (Varela, Thompson, Rosch 1991/2016, Stapleton & Thompson 2009, Di Paolo 2018) and Ecological Psychology focuses on the richness of perceptual experience and the rejection of mind-body and body-world dualisms (Gibson, Richardson, Shockley, Fajen, Riley, and Turvey 2008). Both schools of thought claim that the embodied mind is embedded in its environment, although their stories are not quite the same. I propose that the ways each school of thought relates the mind to the world is a crucially informative point of tension between the two programs. Despite their differences, contemporary enactivism and ecological psychology are converging. I will draw heavily upon Di Paolo, Buhrmann, and Barandiaran’s proposal that embeds the enactive agent in the ecological organism-environment system and reframes enactive constructivism in terms of honing in on relevant affordances in an overabundant environment. I argue that the relationship between the agent and the world, and thus the best way to frame the relationship between the enactive and ecological approaches, is one of complementarity. Nishida’s radical nondualism is built upon the unity of disunity and thus resembles complementarity, and can be used to frame the ecological and enactive approaches through the structure of the present moment. I will apply Nishida’s dialectical analysis to explore the relationship between the enactive agent and the ecological environment as a form of mutual negation. From this comparison, I conclude that the enactive agent and the ecological world can be understood in figure-ground terms, where the enactive agent is the emerging figure that structures and is structured by the ecological world as its ground. I will then consider the insights of the Zen master Dōgen, who developed a notion of nonduality to navigate perplexing contraries, to develop the figure-ground relationship from the mere duality of figure and ground to the complementary contrary, figure~ground exemplified by the Splashed Ink Landscape painting by Sesshū Tōyō. I conclude by suggesting future avenues for cross-cultural cognitive science.